The Influence of Competence and Incentives on Employee Performance at Mazda Indonesia - Purnama, Kurnia Deril; Husainah, Nazifah (GoAcademica Research & Publishing, 2025)
This study aims to analyze the influence of competence and incentives on employee performance at PT Mazda Indonesia. A quantitative research method was employed, involving observation and data collection through the distribution of questionnaires to employees. Data were analyzed using associative hypothesis testing with the aid of SPSS version 23 (Statistical Package for the Social Sciences). Multiple linear regression analysis was utilized to test the hypotheses, and the results indicated that both competence and incentives have a significant effect on employee performance. Statistically, the regression coefficients for both variables demonstrated a positive relationship, implying that improvements in employee competence and incentives lead to enhanced performance. The t-test results showed that the significance value for competence was 0.004 and for incentives was 0.05, confirming that the hypotheses are accepted. The regression analysis further revealed that competence has the most dominant influence in enhancing employee performance. Therefore, it is recommended that the company prioritize employee competence development through training and education, while also providing appropriate incentives to motivate employees toward achieving higher work performance.